The Effect of Ratio of Germinated Mungbeans and Jackfruit’s Seed and Concentration of Tempeh Inoculum on the Quality of Tempeh - Tiopani Yosefin Hutagalung; Rona J. Nainggolan; Mimi Nurminah (Jurnal Rekayasa Pangan dan Pertanian, 2016)
ABSTRACT The aim of this research was to find the effect of ratio of germinated mungbeans and jackfruit’s seed and concentration of tempeh inoculum on the quality of tempeh. The research was using completely randomized design with two factors, i.e ratio of germinated mungbeans and germinated jackfruit’s seed (P): (80%:20%, 70%:30%, 60%:40%, 50%:50%) and concentration of tempeh inoculum (K): (0,5%; 0,75%; 1%; 1,25%). Parameters  analyzed were moisture content (%), ash content (%), protein content (%), fat content (%), crude fiber content (%), score value of colour and texture,  organoleptic value of taste, flavor, and texture. The results showed that the ratio of  germinated mungbeans and jackfruit’s seed had highly significant effect on moisture content, ash content, protein content, fat content, crude fiber content, score value of texture, and organoleptic value of taste. Concentration of tempeh inoculum had highly significant effect on protein content, score value of texture, organoleptic value of texture, and had significant effect on moisture content, ash content, fat content, and score value of colour. Interaction of the two factors had significant effect on protein content and score value of texture. The ratio of germinated mungbeans and jackfruit’s seed of 70%:30% (P2) and concentration of tempeh inoculum of 0,75% (K2) produced the best tempeh. Keywords: Germinated seed, inoculum, jackfruit’s seed, mungbeans, tempeh